The Potential Cost of Cultural Fit: Frame Switching Undermines Perceptions of Authenticity in Western Contexts - West, Alexandria L.; Zhang, Rui; Yampolsky, Maya A.; Sasaki, Joni Y. (Frontiers in Psychology, 2018)
Behaving consistently across situations is fundamental to a person’s authenticity in Western societies. This can pose a problem for biculturals who often frame switch, or adapt their behavior across cultural contexts, as a way of maintaining fit with each of their cultures. In particular, the behavioral inconsistency entailed in frame switching may undermine biculturals’ sense of authenticity, as well as Westerners’ impressions of biculturals’ authenticity. Study 1 had a diverse sample of biculturals (N = 127) living in the US and Canada describe an episode of frame switching (vs. no switching control vs. neutral control) and report on their state authenticity during the episode. Results showed that biculturals recalled feeling less authentic during an instance of frame switching compared to no switching control and neutral control. Study 2 had mainstream Canadians (White and of American, Canadian, or Western European cultural heritage, N = 97) read a hypothetical vignette, from a third-person perspective, about a bicultural who frame switches (vs. no switching control vs. neutral control) and provide their impressions of the bicultural’s authenticity and multiple other desirable traits. Participants rated the bicultural as less authentic when he frame switched compared to no switching control and neutral control, and rated him as less likeable, trustworthy, and warm (but not competent) as downstream consequences of seeing him as less authentic. These results demonstrate that frame switching can come at a cost to authenticity, both in terms of how biculturals see themselves and are seen by others, at least in Western societies. These findings highlight that the way biculturals negotiate their cultures affects them psychologically and socially. In the context of cultural fit, the active process of establishing and maintaining fit with one’s cultures can have unforeseen consequences.